Between Babel and Pentecost: transnational Pentecostalism in Africa and Latin America - Corten, André; Marshall-Fratani, Ruth (Hurst & Co., 2001)
Over the past two decades, Latin American and African countries have experienced a phenomenal growth of Pentecostal movements. This form of Christianity, only marginally present in these areas in the middle of the 20th century, is now embraced by more than a hundred million faithful across two continents and continues to grow at an astonishing rate. Despite the enormous differences which separate these lands and the individual societies within them, one is struck by the similarity of Pentecostal manifestations in these diverse cultures. Contemporary Pentecostalism provides a striking example of the paradox of difference and uniformity, of flow and closure, that seems to be at the heart of processes of transnationalism and globalization. The rapid growth of Pentecostal movements in the urban centers of the developing world has captured the attention of many scholars in the fields of Latin American and African studies. However, much of the literature focuses on individual areas and countries, and there has been relatively little comparative or cross-cultural study of these movements. This book considers the important transnational character of such movements and their tendency to foster identities that transcend national and cultural contexts. Researchers from various disciplines describe Pentecostal movements in Latin America and Africa from different perspectives.